DIVERSIFIKASI PRODUKSI HASIL TANGKAPAN LAUT DALAM MENINGKATKAN PENDAPATAN NELAYAN - Khairunnisa Rangkuti; Sasmitha Siregar; Yolanda Dalimunthe (AGRIUM: Jurnal Ilmu Pertanian, 2013)
Research on the role of sea production diversification to increase of fisherman’s revenues has been conducted, four factors were studied, namely sea mileage, capital, number of diversification, and experience . The study was conducted by using the case study method, by taking a sample of 30 fishermen . Determination of fishermen sampled using stratified random sampling method . To test the hypothesis of the research carried out by using different test average , Regression Analysis , calculated F test , and descriptive analysis . Simultaneously there is a real effect of the distance between the sea , the capital , and the experience of the non- fishing income diversification . Partially, there is no real effect of capital to non- fishing income diversification on the 95% confidence level . In the distance the sea is no real effect of t - calculated value 2.199 > 2.144 and the t - table experience also significantly affect the level of income with indigo 11.865 t count > t - table 2.144 at 95% confidence level . From the test results with the t test , t-test values obtained for mileage at sea is -0.8739 < 2.144 t - table at the 95% confidence level . Capital value of the t test for values obtained 3.7010 t count > t - table 2.144 at 95% confidence level . T test values , for diversification is 109.8938 > t - table 2.144 at 95% confidence level . The results of testing with the t test for the level of experience of the results obtained t - value of -1.0076 count > 2,144 t - table .Keywords : diversification , production , catches , revenues , fishermen